2016
DOI: 10.7567/jjap.55.07kf20
|View full text |Cite
|
Sign up to set email alerts
|

Basic investigation on acoustic velocity change imaging method for quantitative assessment of fat content in human liver

Abstract: Fatty liver is a disease caused by the excess accumulation of fat in the human liver. The early diagnosis of fatty liver is very important, because fatty liver is the major marker linked to metabolic syndrome. We already proposed the ultrasonic velocity change imaging method to diagnose fatty liver by using the fact that the temperature dependence of ultrasonic velocity is different in water and in fat. For the diagonosis of a fatty liver stage, we attempted a feasibility study of the quantitative assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Also, if the transducer is placed anterior to the external acoustic opening, it has been shown that the contact force may change the sound more than 10 dB. 17) Unlike other transducers for nondestructing inspection or clinical assessment, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the bone-conducted sound transducer does not use matching materials and the sound propagation is relatively affected by the contact force. The contact force should be monitored for consistent and reproducible experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Also, if the transducer is placed anterior to the external acoustic opening, it has been shown that the contact force may change the sound more than 10 dB. 17) Unlike other transducers for nondestructing inspection or clinical assessment, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] the bone-conducted sound transducer does not use matching materials and the sound propagation is relatively affected by the contact force. The contact force should be monitored for consistent and reproducible experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, other applications of ultrasonic transducers are rigidly connected to the material or utilize matching materials such as water. [11][12][13][14][15][16][17][18][19][20][21][22] Previously, many studies on BC sounds reported that the contact force of the BC transducer or hair between the skin and the BC transducer may affect perception. [23][24][25][26][27] Although the relationship between the contact force of the BC transducer and perception has been studied for many years, there is no single contact force for all purposes, as the optimal contact force strongly depends on usage.…”
Section: Introductionmentioning
confidence: 99%
“…When biological tissue is exposed to ultrasound, the temperature rises depending on physical parameters that are inherent to the tissue such as specific heat, thermal diffusion coefficient, attenuation coefficient as well as ultrasonic intensity. [9][10][11][12][13][14] Tissue characterization based on the rate of temperature rise due to ultrasonic heating has been proposed. 10,11) This method has the potential to facilitate the in vivo evaluation of the volumetric distribution of Lipiodol ® inside tumors since Lipiodol ® primarily consists of poppy-seed oil.…”
mentioning
confidence: 99%